Revealing gender differences in concussion reporting: a detailed analysis of SCAT assessment self-report symptom ratings - Edelstein, Rachel; Schmidt, Karen M.; Van Horn, John Darrell (Frontiers in Neurology, 2025)
IntroductionCurrent concussion assessments used by the NCAA are generally applied to both male and female athletes to evaluate the effects of sports-related head impacts. However, increasing evidence indicates that female athletes show different physiological and psychosocial responses to concussions compared to their male counterparts, raising concerns about the suitability of gender blind concussion assessments.MethodsThis study analyzes data from N = 1,021 NCAA athletes (379 females, 642 males) who completed the SCAT3 Symptom Severity Checklist after a concussion. A systematic use of multivariate statistical methods, including Exploratory Graph Analysis (EGA), Principal Component Analysis (PCA), Exploratory Factor Analysis (EFA), Linear Discriminant Analysis (LDA), and Rasch Partial Credit Modeling (PCM), was applied to this 22-item instrument to explore the underlying factor structure and identify assessment items sensitive to gender differences. Differential Item Functioning (DIF) analysis examined gender disparities in symptom reporting.ResultsBased on EGA and PCA, the SCAT3 showed a four-factor substructure, with EFA accounting for 62.44% of the variance. LDA comparing males and females revealed a significant difference in their multivariate score distributions (χ2 (22) = 130.56, p < 0.001), with emotional and physical symptom items loading negatively, and cognitive and sensory items loading positively. This suggests emotional and physical symptoms contribute oppositely to cognitive and sensory symptoms, implying these domains may represent opposite ends of a single symptom dimension. Rasch analysis of each assessment item identified three items with no difference between genders. Conversely, nine symptoms showed males were more likely to report higher severity. Nonetheless, females generally reported divergent overall symptom severity scores (Mean = 30.06, SD = 20.88) than males (Mean = 24.71, SD = 21.18), t(765.06) = 3.85, p < 0.001.DiscussionDifferences in symptom presentation post-concussion may suggest that: (1) males tend to be more conservative in reporting and only endorse symptoms when they are more intense, leading to higher scores on fewer symptoms, whereas (2) females may more readily emphasize emotional and physical symptoms. The findings imply that considering gender differences in concussion symptom reporting is important when making clinical recommendations.